2020
DOI: 10.1016/j.biopsych.2019.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evidence for Predispositional Effects of Brain Gray Matter Volume on Alcohol Consumption

Abstract: Background: Alcohol use has been reliably associated with smaller subcortical and cortical regional gray matter volumes (GMVs). Whether these associations reflect shared predisposing risk factors and/or causal consequences of alcohol use remains poorly understood.Methods: Data came from 3 neuroimaging samples (total n=2,423), spanning childhood/adolescence to middle age, with prospective or family-based data. First, we identified replicable GMV correlates of alcohol use. Next, we used family-based and longitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 69 publications
2
45
0
Order By: Relevance
“…For example, our LDSC based enrichment analysis shows that GWAS variants for both AUD and DPW are enriched in the genes expressed during early brain development. Drinking in later years might interact with this genetic predisposition making individuals more susceptible not only to AUD but also to other neuropsychiatric disorders 32 . Identification of SPI1 and MAPT as genes for AUD are good examples of pleiotropy and/ or causal links between the alcohol intake and susceptibility to AUD, other psychiatric disorders (e.g., depression) and even Alzheimer's disease 15,33 and other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our LDSC based enrichment analysis shows that GWAS variants for both AUD and DPW are enriched in the genes expressed during early brain development. Drinking in later years might interact with this genetic predisposition making individuals more susceptible not only to AUD but also to other neuropsychiatric disorders 32 . Identification of SPI1 and MAPT as genes for AUD are good examples of pleiotropy and/ or causal links between the alcohol intake and susceptibility to AUD, other psychiatric disorders (e.g., depression) and even Alzheimer's disease 15,33 and other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Human neuroimaging studies indicate that early onset of alcohol use and BD in adolescents or emerging adults are linked to aberrations in brain structure relative to healthy controls (HCs) ( Lees et al, 2020 , Squeglia and Cservenka, 2017 ). The identified deviations in brain structure include, for example, reduced cortical thickness ( Brumback et al, 2016 ), decreased surface area ( Infante et al, 2018 ), and increased grey matter (GM) densities ( Sousa et al, 2017 ) in frontal regions, and a GM volume reduction in multiple regions ( Baranger et al, 2020 , Squeglia et al, 2014 , Yang et al, 2016 ) with exceptions including greater striatal volume ( Howell et al, 2013 ). Gender-related effects have also been observed, with cortical thickness in selected frontal regions thinner in males, and thicker in females ( Squeglia et al, 2012 ); and putamenal volumes smaller in males, and larger in females who report early onset of alcohol use or BD, relative to controls ( Fein et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects from both groups had no or limited access to alcohol, eliminating the effects of alcohol as a confounder. A large neuroimaging study with 2,423 individuals also found a smaller right dorsolateral prefrontal cortex and insula GM volumes were associated with increased alcohol use, thus providing further support that a reduction in cortical thickness may be an AUD risk factor ( Baranger et al, 2019 ). Family based and prospective longitudinal data suggested this association is of genetic origin and that smaller GM volumes could serve as a prognostic biomarker for AUD.…”
Section: Alcohol Alters the Morphology And Physiology Of The Brainmentioning
confidence: 86%
“…These inconsistencies in anatomical boundaries generate confusion as unique structural specific activities and responses identified in rodents are then ascribed to the incorrect human brain region ( Laubach et al, 2018 ). Rodents lack the homologous structures to the dorsolateral prefrontal regions, which exhibit pronounced vulnerability to alcohol ( Preuss, 1995 ; Miguel-Hidalgo et al, 2002 ; Chanraud et al, 2007 ; Makris et al, 2008 ; Baranger et al, 2019 ). Consequently, rodents provide less information pertaining to alcohol induced pathophysiology and overall effect on the dorsolateral prefrontal region ( Preuss, 1995 ).…”
Section: Discussion: a Translational Porcine Model Provides Potentialmentioning
confidence: 99%
See 1 more Smart Citation